The best of America's Test Kitchen : best recipes, equipment reviews, and tastings 2018 / the Editors at America's Test Kitchen. (America's Test Kitchen, 2017)
The best of the best--including recipes, tastings, and testings--from the current year, all compiled into one must-have collection from America's most trusted test kitchen.